2020
DOI: 10.1155/2020/7981791
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impacts of Autonomous Bus-on-Demand Based on Agent-Based Simulation: A Case Study of Fuyang, Zhejiang, China

Abstract: This paper envisions and assesses the performance of an autonomous bus-on-demand (ABoD) system. We take Fuyang, Zhejiang, China, as the study area to investigate the spatiotemporal distribution of bus travel demand during workdays, and we propose replacing inefficient bus routes with the ABoD system. Agent-based models with various bus dispatching and operation control strategies are constructed to evaluate the performance of the ABoD system. The behaviors and interactions of the agents, passengers, autonomous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Another approach may be to give people the feeling that they have influence over the bus route, e.g., by selfefficaciously requesting a bus via app. These on-demand services are currently being simulated and tested for several cities, e.g., Hamburg, Germany [51] or Fuyang, China, [52], and might have a positive impact on the perceived self-efficacy. Providers should also emphasize the benefits of AVs and inform passengers specifically, e.g., opportunities related to driving safety or optimizing traffic flow [12,53].…”
Section: Summary and Practical Implicationsmentioning
confidence: 99%
“…Another approach may be to give people the feeling that they have influence over the bus route, e.g., by selfefficaciously requesting a bus via app. These on-demand services are currently being simulated and tested for several cities, e.g., Hamburg, Germany [51] or Fuyang, China, [52], and might have a positive impact on the perceived self-efficacy. Providers should also emphasize the benefits of AVs and inform passengers specifically, e.g., opportunities related to driving safety or optimizing traffic flow [12,53].…”
Section: Summary and Practical Implicationsmentioning
confidence: 99%
“…The model found savings in total passenger travel time and the number of vehicles over existing routes. Similarly, ordinary fixed routes with skipping capabilities were proposed based on origin–destination generated from payment data in Zhejiang, China ( 16 ). Agent-based simulation, which incorporated the interaction of passengers, buses (in operation/idle), and control center, concluded that the proposed model offered higher utilization of buses and better adaptiveness to changes in demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wagner [23] demonstrates through traffic simulation studies that autonomous systems reduce intersection delays by 5-80%. Zhai et al study the impact of replacing one bus line with an automated bus on-demand system in Fuyang prefecture in China, and find the system overwhelmingly advantageous, with less road resource occupation, shorter passenger waiting times and more efficient utilization of vehicle capacity [24]. However, a microscopic traffic simulation by Arnaout and Arnaout [25] suggests that capacity gains are not significant under a low to moderate penetration rate of AVs.…”
Section: Will the Shift Augment Or Curtail Traffic Flow?mentioning
confidence: 99%
“…In an agent-based simulation of Manhattan, the estimated cost for the operation of an SEAV fleet is roughly ten times lower than a regular taxi fare, as a result of savings due to electrification, the elimination of driver cost and efficiency of a single-operator, smartphonebased system [32]. Zhai et al compare a traditional bus system with an automated bus on-demand (ABoD) system and find that if the travel demand exceeds five multiples of the current demand, the total cost of conventional buses increases sharply, while the cost of the ABoD increases almost linearly, which indicates that the ABoD system is more adaptive to the change in travel demand than the conventional buses [24].…”
Section: Will the Shift Increase Or Decrease The Cost Of Travel?mentioning
confidence: 99%
See 1 more Smart Citation